Substrate use and biochemical response to a 3,211-km bicycle tour in trained cyclists - Slivka, D. R.; Dumke, C. L.; Hailes, W. S.; Cuddy, J. S.; Ruby, B. C. (European Journal of Applied Physiology, 2012)
The purpose of this study was to assess the physiological adaptations in physically fit individuals to a period of intensified training. Ten trained males cycled outdoors ~170 km day-1 on 19 out of 21 days. Expired gas was collected on days 1 and 21 during maximal graded exercise and used for the determination of gross efficiency and whole body substrate use. Muscle biopsies were obtained before and after exercise on days 2 and 22 for the determination of mtDNA/gDNA ratio, gene expression, metabolic enzyme activity and glycogen use. Muscle glycogen before and after exercise, fat oxidation, and gross efficiency increased, carbohydrate oxidation decreased (p < 0.05), and VO2max did not change over the 21 days of training. Citrate synthase (CS), ß-hydroxyacyl CoA dehydrogenase (ß-HAD) and cytochrome c oxidase (COX) enzyme activity did not change with training. CS and ß-HAD mRNA did not change with acute exercise or training. COX (subunit IV) mRNA increased with acute exercise (p < 0.05) but did not change over the 21 days. PGC-1a mRNA increased with acute exercise, but did not increase to the same degree on day 22 as it did on day 2 (p < 0.05). UCP3 mRNA decreased with training (p < 0.05). Acute exercise caused an increase in mitofusin2 (MFN2) mRNA (p < 0.05) and a trend for an increase in mtDNA/gDNA ratio (p = 0.057). However, training did not affect MFN2 mRNA or mtDNA/gDNA ratio. In response to 3,211 km of cycling, changes in substrate use and gross efficiency appear to be more profound than mitochondrial adaptations in trained individuals.